Job stress among nurses in tertiary care hospital: identifying risk factor of poor mental health - Jiju, Liji; Singh, Maharaj (International Journal of Research in Medical Sciences, 2022)
Background: Occupational stress may have a negative effect on an employee's health when workplace stresses outweigh the capacity of an employee to exercise some control over their job or cope in those other ways. Nurses experience stress and health difficulties as a result of the nature of their employment, their interaction with patients, and their exposure to mortality. Given that emotions may influence job results, emotional intelligence (EI) may help explain why individuals respond differently to work stress. Methods: The approach adopted for this study is quantitative research approach. A descriptive research design was taken to identify the study sample which were 105 staff nurses selected by non-probability purposive sampling technique. Occupational stress assessment was measured using the Srivastava and Singh (1984) occupational stress index. Results: It was seen that occupational stress level among staff nurses. 60% participants showed the moderate stress level score (116-161) followed 36.2% in high level (more than 161) and 3.8% depicted low stress (71-115). No one expressed that there is no stress. Type of hospital administration showed a significant association with occupational stress. Conclusions: The study concluded that the present study emphasis that majority of the nurses working in hospital at Pune city are affected with occupational stress and don’t bear good psychological wellbeing. Occupational Stress has become the most important factor influencing individual efficacy and satisfaction in modern day work environment. Nursing profession is increasingly characterized by high occupational stress.